Perlindungan Hukum Bagi Pemilik Dan Penghuni Apartemen Atas Kenaikan IPL Secara Sepihak Oleh Pengelola - Gunawan, Ricky Wijaya (Magister Kenotariatan Universitas Surabaya, 2024)
Apartment or condominium is one of many solutions for residence availability on today’s problem of population density and limited land. According to Act Number 20 of 2011 on Condominium, condominium management is done by the development actors before the Association of Owners and Tenants of Condominium Units (later stated as PPPSRS) is created. The owners and tenants of condominium units have obligation to pay monthly maintenance fees to condominium manager for upkeep and maintenance of condominium. Condominium manager has obligation to manage the monthly maintenance fees with the implementation of principle of transparancy. In the case of Apartment X which is located in Surabaya, the condominium manager (PT Y) raised the monthly maintenance fees without the principle of transparancy to the owners and tenants of Apartment X. PT Y’s decision of raised the monthly maintenance fees without the principle of transparancy is an act of tort, according to Indonesian Civil Law (KUHPerdata). The owners and tenants of Apartment X had lodge a protest and tried to mediate with PT Y about the raise of monthly maintenance fees but failed. The owners and tenants of Apartment X have the rights to get legal protection and legal guarantee due the act of tort of PT Y.